Experiences of child sexual abuse survivors with formal child protection systems: An indigenist perspective (Journal of Comparative Social Work, 2025)
Preventing abuse in childhood and providing services to the victims requires a comprehensive child protection framework. Even when the government of Uganda has made deliberate efforts to facilitate protection of children, research shows that their efforts have largely been inadequate. Adopting an indigenous perspective that centers the structural inequalities that inform social relationships in families, communities and the society rather than the individual is paramount. Thus, this study examined how indigenous child protection systems can be integrated to complement formal approaches in responding to child sexual abuse. This article presents experiences of five adult women from Luuka district, Uganda who experienced rape during their childhood. Narrative inquiry was used to explore survivors’ experiences. This information was complemented by information from social workers who were purposively selected and interviewed using a semi-structured interview guide. Thematic analysis was used to analyse the findings and four major themes relating to survivors’ experiences emerged from this study. Survivors reported challenges with investigations, access to justice, lack of protective shelter and challenges in accessing medical services. In addition to formal child protection systems, survivors utilised services from indigenous child protection systems which included; Local Council 1, community volunteers, social groups and savings groups. Indigenous practices based on mutual aid and community organising addressed broader welfare needs of survivors, including enabling them to access education, linkage to services and access to shelter. The social support provided through indigenous models involved multiple social welfare functions, and addressed different child protection needs. However, poverty at the household and community level limits the scalability of such approaches. Accessing formal child protection services was found to be costly for the survivors. The Informal Child Protection System is more accessible, offers comprehensive services and demonstrates to buffer the formal systems.